(untitled) (LACCEI, 2024)
Animation is an ideal resource for storytelling, and in the audiovisual world it allows transmitting messages and emotions beyond the senses. Therefore, the present research aims to analyze the research of the last ten years on semiotics and audiovisual narrative in animated series and films. To achieve this, it conducted a systematic review (SLR) of scientific articles in the Scopus, EBSCO, ScienceDirect and ProQuest databases, in the Dialnet and Redalyc repositories, and the Google Scholar search engine. After the inclusion and exclusion process, which contemplated criteria such as language, field of study and year of publication, 41 research papers published between 2012 and 2022 were found. Among the main results, it stands out that most of the studies belong to Spain and that there was an increase in articles between 2018 and 2021. Regarding limitations, the lack of publications in Latin America and languages other than English and Spanish were emphasized. In conclusion, semiotics and audiovisual narrative in animation is a moderately studied field and its importance is evidenced by the deep research of the authors.